If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying logx + log(x + 2) = log(3x) Reorder the terms: glox + glo(2 + x) = log(3x) glox + (2 * glo + x * glo) = log(3x) glox + (2glo + glox) = log(3x) Reorder the terms: 2glo + glox + glox = log(3x) Combine like terms: glox + glox = 2glox 2glo + 2glox = log(3x) Remove parenthesis around (3x) 2glo + 2glox = glo * 3x Reorder the terms for easier multiplication: 2glo + 2glox = 3glo * x Multiply glo * x 2glo + 2glox = 3glox Solving 2glo + 2glox = 3glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-3glox' to each side of the equation. 2glo + 2glox + -3glox = 3glox + -3glox Combine like terms: 2glox + -3glox = -1glox 2glo + -1glox = 3glox + -3glox Combine like terms: 3glox + -3glox = 0 2glo + -1glox = 0 Factor out the Greatest Common Factor (GCF), 'glo'. glo(2 + -1x) = 0Subproblem 1
Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing g to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Add 'x' to each side of the equation. -1x + x = -2 + x Combine like terms: -1x + x = 0 0 = -2 + x Simplifying 0 = -2 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 10n+7-3n+5= | | (n+6)=(3n-10) | | -480=-8(4-7r) | | (-5)9x-15=-465 | | 5-3x+8x=6-2x+3x | | -x^2-6x-10=-1 | | f(x)=2tanx | | 4n-2-7n=20 | | -4[x+2(5xy-x)]= | | X(2)+4x-2=0 | | 25+7.5w=250 | | f(x)=-7x^2+9x+1 | | (6w^2-3w+1)-(w^2+w-9)= | | 40+M=100 | | 8k-40=1+6 | | 11.3l-10.3l+7=13.24 | | 2(3x-1)=6x+7-2 | | 3x+1y=8 | | 20x+180=10x-70 | | 7a^3+4a-12= | | 8x-72=24x+8 | | 3x+3+7x=-51 | | 5x^2-9x-30=0 | | 6y+3-2y=2y+11+4y | | 46=2v | | x^2-208x-29440=0 | | 5u+3u= | | -0.6(r+.2)=1.8 | | 13x-8=-32 | | -12=132 | | 5(4n+9)=-3 | | y=sin^1x^3 |